Evaluation of antioxidant and gastroprotector activities of Moringa oleifera - Galdino, Fernanda Silva (2021)
Moringa oleifera is a tree plant species and its different parts are used in folk medicine as anti-inflammatory, in the treatment of respiratory diseases and gastrointestinal tract. This study aims to perform a phytochemical screening of the ethanolic extract of Moringa oleifera leaves and evaluate its antioxidant and gastroprotective activities. Phytochemic a screening was performed by phenol and total flavonoid dosage; antioxidant activity was evaluated in in vitro models by 2,2-diphenyl-1-picrylhydrazil (DPPH) peroxidation methodologies and gastroprotective activity was evaluated. by the acute induction methodology of gastric ulcer using ethanol PA The phenol content for the study extract was calculated as 128.4 + 14.42 mg EAG/g extract. The flavonoid content was mg EQ / 100 g extract. All concentrations of the extract exhibited antioxidant activity, with the highest free radical sequestration capacity being attributed to a concentration of 1000 mg / mL with 71.39 ± 0.52. In the study of gastroprotective activity, the dose of 200 mg / kg presented an inhibition of ulcerative lesion of 48.48% in relation to the control. Acute toxicity tests did not show significant changes between the negative control group and the group treated with EEMo at a dose of 1000 mg/kg. The results show that the ethanolic extract of Moringa oleifera leaves has gastroprotective activity, possibly due to high content of phenols, flavonoids and antioxidant activity present in the extract.